Evaluation of Integrated Heat Wave Vulnerability Parameters in Indian Context - Sharma, Vidushi (Calibrating Urban Livability in the Global South, 2024)
A heat wave is a disaster that has started to become a concern due to its increase in frequency and heat waves that last longer and are more powerful are occurring more frequently worldwide. India is also seeing the effects of climate change in the form of an increase in the frequency of heat waves, which are becoming more extreme and have a catastrophic effect. Like other calamities, the severity of a high heat event relies on how vulnerable the population is. Thus, it is essential to understand the parameters and factors that help mitigate such a calamity and prevent it from becoming a disaster leading to loss of life. The paper tries to understand the factors which affect the heat wave vulnerability of a place thus coming up with an integrated parameters for assessment of the heat wave vulnerability. Thus, after analyzing various literature and parameters which are used, the paper concludes that the data can be categorized into 19 parameters under Exposure, 11 parameters under Sensitivity and 9 characteristics under Adaptive Capacity which can be utilized for the evaluation of Integrated Heat wave Vulnerability Index parameters in Indian Context.